Magnetic reconnection in the near‐Mars magnetotail: MAVEN observations. Issue 21 (5th November 2015) - Harada, Y.; Halekas, J. S.; McFadden, J. P.; Mitchell, D. L.; Mazelle, C.; Connerney, J. E. P.; Espley, J.; Larson, D. E.; Brain, D. A.; Andersson, L.; DiBraccio, G. A.; Collinson, G. A.; et al.
Abstract: We report Mars Atmosphere and Volatile EvolutioN (MAVEN) observations of electrons, ions, and magnetic fields which provide comprehensive demonstration of magnetic reconnection signatures in the Martian magnetotail. In the near‐Mars tail current sheet at X MSO ∼−1.3 R M, trapped electrons with two‐sided loss cones were observed, indicating the closed magnetic field topology. In the closed field region, MAVEN observed Hall magnetic field signatures and Marsward bulk flows of H +, O +, and O 2 + ions, which suggest the presence of X lines tailward from the spacecraft. Velocity distribution functions of the reconnection outflow ions exhibit counterstreaming beams separated along the current sheet normal, and their bulk velocities in the outflow direction inversely depend on ion mass. These characteristics are in qualitative agreement with previous multispecies kinetic simulations. The near‐Mars magnetotail provides a unique environment for studying multi‐ion reconnection. Key Points: We present comprehensive MAVEN observations of magnetic reconnection at Mars The observed signatures are consistent with previous multispecies PIC simulations Mars provides a unique environment for investigation of multi‐ion reconnection